Kajian Hukum Pencemaran Danau Siombak Atas Dampak Pembuangan Bangkai Babi Yang Terkena Virus Hog Cholera Ditinjau Dari Aspek Lingkungan Hidup Undang Undang Nomor 32 Tahun 2009 (Studi Di Lingkungan Hidup Kota Medan) - M.Yusril Mahendra Butar-Butar; Ridho Mubarak; Revi Fauzi Putra Mina (ARBITER: Jurnal Ilmiah Magister Hukum, 2022)
A good and healthy environment is the basic right of every Indonesian citizen as stated in Article 28 H of the 1945 Constitution of the Republic of Indonesia. The environment is a spatial unit with all objects, forces, conditions, living things, including and their behavior, which affects nature. itself, continuity in life and welfare. Based on the above background, the problems that will be examined in this study are as follows, How is the criminal responsibility that has contaminated the pig disposal in the area of Lake Siombak based on Law Number 32 Year 2009, and How is the means of supporting obstruction in law enforcement efforts against perpetrators environmental crime. environmental crime is contained in the formulation of law no. 32 of 2009 concerning protection and management of the environment in the form of administrative sanctions, criminal sanctions and civil sanctions, so the supporting facilities in this case of environmental pollution are the police conducting patrols in the area of Medan city law as well as briefing the regional government. Medan city community to inform if there are breeders affected by the hog cholera virus.